Penyusunan Anggaran Penjualan Keramik (Ceramic Tiles) pada Toko Aira Mandiri Group Kota Langsa menggunakan Metode Trend Moment - Muhammad Fuad; Dina Novita (STIE Malangkucecwara, 2016)
The development of Langsa City that followed the construction of various infrastructureincreasing the market demand for building materials, particularly ceramic tile products. As one of the stores that specialize in selling ceramic tiles in the city, Toko Aira Mandiri Group should be able to anticipate the situation through sales budgeting carefully and accurately. The use of trend moment method for predicting future sales volumes in preparing the sales budget is based on two main reasons. The results of this study showed that the implementation of trend moment method in arrangingsales budget helps Toko Aira Mandiri Group predicts future sales volume and therefore be able to plan the inventory level of ceramic tile products it offers in order to avoid losses due to shortage or surplus of inventory. The sales budget can also be used as a reference in formulating business strategies to see which market trend or seasonal conditions towards company’s ceramic tiles.